Self-determination Theory as a Lens to Explore the Implementation Challenges of Telehealth - Yafit Gilboa; Michal Pagis; Kathleen Lyons (International Journal of Telerehabilitation)
Many benefits can be gained from telehealth, including reduced travel time, flexible work schedules, increased patient satisfaction, and a cost-effective method of providing care. Furthermore, telehealth provides rehabilitation professionals with the opportunity to observe people in their natural environment as they conduct their daily activities and identify any barriers to their functioning. Despite these advantages, and after a substantial amount of research supporting its effectiveness, telehealth remains relatively underutilized.